Behavior of Broilers Reared under Monochromatic and Fluorescent Light Sources - Eich , Mayara Rodrigues de Santana; Garcia, Rodrigo Garofallo; Naas, Irenilza de Alencar; Caldara, Fabiana Ribeiro; Borille, Rodrigo; Royer, Ana Flavia Basso; Sgavioli, Sarah (International Journal of Poultry Science, 2016)
The study aimed to evaluate the behavior of broiler chickens reared in the blue and red light emitting diode (LED), using a fluorescent light as a control. The bird behaviors were recorded at 28, 35 and 42 d of grow-out using video clips. Broilers were randomly distributed in a factorial arrangement of 2 x 3 (two sex and three light sources) using six treatments and four replications. Blue and red LED light source and fluorescent light were tested from the 10th day until the 42nd day of grow-out. Behavioral data were analyzed using ANOVA and Kruskal-Wallis test was applied. An association was found between bird age, sex and source of light in the eating, drinking, preening and foraging behavior. Broilers were more active when exposed to fluorescent light and red LED than the birds exposed to the blue LED light source.